Burnout in Nurses: How Job Redesigns Can Help - Moses Siruri Marwa; Jane Muthoni Kinuthia (European Scientific Journal, ESJ, 2025)
Burnout is a common phenomenon in many modern-day organizations. The literature, however, shows that burnout is more pronounced in nurses relative to other categories of healthcare workers.  Unfortunately, there is a dearth in the literature on how organization development interventions can help reduce burn out in nurses. This paper accordingly attempts to examine the ways job redesigns can be appropriated as typologies of organization development interventions, the overarching goal being to propose dimension-specific interventions of job redesigns that can subsequently be empirically tested as predictors in studies, towards understanding of how to reduce burnout experiences in nurses in their everyday undertaking of caregiving.